The Diagnosis and Treatment of a Mycotic Coronary Artery Aneurysm: A Case Report. Issue 10 (13th August 2013) - Pfahl, Kyle W.; Orsinelli, David A.; Raman, Subha; Firstenberg, Michael
<x xml:space="preserve">Abstract</x> Aneurysms of the coronary arteries are rare and are usually associated with atherosclerosis in adults. Mycotic coronary artery aneurysms are exceedingly uncommon and are typically associated with systemic bacteremia, endocarditis, or septic emboli. Literature and data describing the management of mycotic coronary artery aneurysms are limited. This case describes the successful diagnosis of a large right coronary artery aneurysm by transesophageal echocardiogram as well as the successful management of the aneurysm.